Doped Graphene for DNA Analysis: the Electrochemical Signal is Strongly Influenced by the Kind of Dopant and the Nucleobase Structure - Tian, Huidi; Wang, Lu; Sofer, Zdenek; Pumera, Martin; Bonanni, Alessandra (Scientific reports, 2016)
Doping graphene with heteroatoms can alter the electronic and electrochemical properties of the starting material. Contrasting properties should be expected when the doping is carried out with electron donating species (n-type dopants) or with electron withdrawing species (p-type dopants). This in turn can have a profound influence on the electroanalytical performance of the doped material being used for the detection of specific probes. Here we investigate the electrochemical oxidation of DNA bases adenine, guanine, thymine and cytosine on two heteroatom-doped graphene platforms namely boron-doped graphene (p-type dopant) and nitrogen-doped graphene (n-type dopant). We found that overall, boron-doped graphene provided the best response in terms of electrochemical signal sensitivity for all bases. This is due to the electron deficiency of boron-doped graphene, which can promote the oxidation of DNA bases, as opposed to nitrogen-doped graphene which possesses an excess of electrons. Moreover, also the structure of the nucleobase was found to have significant influence on the obtained signal. Our study may open new frontiers in the electrochemical detection of DNA bases which is the first step for label-free DNA analysis.
Keywords: grafit; sekvenční analýza DNA; Sequence Analysis, DNA; elektrochemické techniky; DNA; Graphite; Electrochemical Techniques